Metal Tools in Unpublished Cuneiform Texts from Early Dynastic Period - Ali Abdul Malik, Munther; Saad Salih, Israa (Al-Adab Journal, 2020)
The people in ancient Mesopotamia know many minerals (Metal Tools) , and they also know how to manufacture it and used them . Minerals have entered in many of their businesses and industries , even in the field of producing artworks (artifacts) . Pots and agricultural tools as well as weapons they used in everyday life .The most important of these metals are : gold , silver , copper , and tin , which some of them entered in the work of bronze bullion (Al-Jader , 1991 , p.225) .The ancient Mesopotamians struggled to get the materials , they were carrying the tired journeys in order to bring the raw materials from far away counties , among them were Dilmun , Magan , Meluhha , Eygpt and Anatolia (Levy , 1986 , p.19) .So we did not care about the all kinds of minerals , but we define our works about one type of this metals , which is a copper metal . So the copper regarded the first mineral which known to the people of ancient Mesopotamia , they used it very much in their lives , this had been a major turning point in the history of their civilization (Louis , 2008 , p.112) .